Biochar application mode influences nitrogen leaching and NH3 volatilization losses in a rice paddy soil irrigated with N-rich wastewater. Issue 16 (18th August 2018) - Sun, Haijun; Min, Ju; Zhang, Hailin; Feng, Yanfang; Lu, Kouping; Shi, Weiming; Yu, Min; Li, Xuewen
ABSTRACT: Impacts of biochar application mode on nitrogen (N) leaching, ammonia (NH3 ) volatilization, rice grain yield and N use efficiency (NUE) are not well understood. Therefore, a field experiment was conducted to evaluate those impacts in a rice paddy soil received 225 kg N ha −1 from either urea or N-rich wastewater. One treatment received 10 t ha −1 biochar with the basal fertilization, and the other received same total amount of biochar but split applied with the three split N applications with same ratio as N fertilizer split ratio (40%, 30% and 30%). Results showed that N leaching loads were 4.20–6.22 kg ha −1 . Biochar one-time application reduced N leaching by 23.1%, and biochar split application further reduced N leaching by 32.4%. Total NH3 volatilization loss was 15.5–24.5 kg ha −1 . Biochar one-time application did not influence the NH3 volatilization, but biochar split application stimulated the cumulative NH3 volatilization by 57.7%. Both biochar treatments had no influence on NUE and rice grain yield. In conclusion, biochar application mode indeed influences the N leaching and NH3 volatilization in rice paddy soils, and biochar one-time application should be recommended for reducing N leaching without increasing NH3 volatilization.